Estimation of thermal effects of fouling growth for application in the scheduling of heat exchangers cleaning. (5th January 2021) - Trafczynski, M.; Markowski, M.; Urbaniec, K.; Trzcinski, P.; Alabrudzinski, S.; Suchecki, W.
Highlights: Fouling reduces heat recovery in heat exchanger networks (HENs) if not cleaned. 3 methods to estimate thermal resistance of fouling ( Rf ) in HEN are used. Case study allows to compare reliability of Rf predictions based on these methods. Energy savings due to hypothetical schedules of HEN cleaning are also evaluated. Measurement-aided method to determine Rf is suitable for use in cleaning scheduling. Abstract: Energy-saving heat recovery in an industrial heat exchanger network may by impaired by fouling build-up on heat transfer surfaces of the exchangers. During longer periods of network operation, monitoring of fouling growth based on measurement data makes it possible to schedule and perform exchanger cleaning if needed for the mitigation of adverse effects of fouling. Three different methods of measurement-aided fouling monitoring are outlined: two simple methods known from literature and a least-squares based method introduced by the authors. A case study is performed on their hypothetical application in a real-life network of shell-and-tube heat exchangers used for heat recovery in crude distillation unit. Using historical measurement data recorded during three-year continuous operation of the network, the different methods are first employed to estimate the thermal effects of fouling and then used in the simulation of attainable energy and economic savings resulting from two alternative options of cleaning interventions in the network. The least-squares based method of measurement-aided fouling monitoring is identified as best suited for the evaluation of effectiveness of cleaning interventions in heat exchanger networks.